ANALISIS FAKTOR YANG MEMENGARUHI AGLOMERASI INDUSTRI UNGGULAN DAERAH DAN HUBUNGANNYA DENGAN DAYA SAING INDUSTRI DAERAH - Fikanti Zuliastri; Wiwiek Rindayati; Alla Asmara (IPB University, 2013)
The manufacturing industry sector is a major driver of economic growth in Indonesia with the largest contribution to the components of Gross Domestic Product is 25.60 % in 2012. But the globalization and liberalization of international trade requires industries to be more competitive. Improving the competitiveness of the industry can be done through the development of regional-based industrial sector main industry that area. The purpose of this study was to analyze the competitiveness and industrial agglomeration, the causality relationship between competitiveness and agglomeration industry and the factors that influence agglomeration of province main industries. This study was using large and medium scale industry raw data. The data analysis using Location Quotient, Hoover Balassa Index, Granger Causality method and panel data method with Fixed Effect Model. The result of panel data regression shows factors that influence the agglomeration of province main industries are firm size, value added, the diversity of industry, industry competition index, competitiveness index, wages and road infastructure. Keywords: Agglomeration, Granger Causality, Industrial Competitiveness, Panel Data